FOCAL AND ABERRANT PREFRONTAL ENGAGEMENT DURING EMOTION REGULATION IN VETERANS WITH POSTTRAUMATIC STRESS DISORDER. Issue 10 (22nd February 2014) - Rabinak, Christine A.; MacNamara, Annmarie; Kennedy, Amy E.; Angstadt, Mike; Stein, Murray B.; Liberzon, Israel; Phan, K. Luan
<x xml:space="preserve">Abstract</x> Background Collectively, functional neuroimaging studies implicate frontal–limbic dysfunction in the pathophysiology of posttraumatic stress disorder (PTSD), as reflected by altered amygdala reactivity and deficient prefrontal responses. These neural patterns are often elicited by social signals of threat (fearful/angry faces) and traumatic reminders (combat sounds, script‐driven imagery). Although PTSD can be conceptualized as a disorder of emotion dysregulation, few studies to date have directly investigated the neural correlates of volitional attempts at regulating negative affect in PTSD. Methods Using functional magnetic resonance imaging and a well‐validated task involving cognitive regulation of negative affect via reappraisal and known to engage prefrontal cortical regions, the authors compared brain activation in veterans with PTSD (n = 21) and without PTSD (n = 21, combat‐exposed controls/CEC), following military combat trauma experience during deployments in Afghanistan or Iraq. The primary outcome measure was brain activation during cognitive reappraisal (i.e., decrease negative affect) as compared to passive viewing (i.e., maintain negative affect) of emotionally evocative content of aversive images Results The subjects in both groups reported similar successful reduction in negative affect following reappraisal. The PTSD group engaged the dorsolateral prefrontal cortex (dlPFC) during cognitive reappraisal, albeit to a lesser extent than the CEC group. Although the amygdala was engaged in both groups during passive viewing of aversive images, neither group exhibited attenuation of amygdala activation during cognitive reappraisal. Conclusions Veterans with combat‐related PTSD showed less recruitment of the dlPFC involved in cognitive reappraisal, suggesting focal and aberrant neural activation during volitional, self‐regulation of negative affective states.